Literasi dan Steam Pada Kurikulum Merdeka Belajar Melalui Taksonomi Bloom - Muhibbah Suraiya Irham (AR-RASYID : Jurnal Pendidikan Agama Islam, 2022)
The cognitive domain of intellectual potential consists of knowledge, understanding, application, analysis, synthesis, evaluation, analysis, synthesis, evaluation in the learning process and learning evaluation found by a researcher, namely. These are all related to the task of the teacher or instructor and are very important in learning, achievement. One of the learning outcomes that must be developed in early childhood education is literacy and STEAM (Science, technology, engineering the arts of mathematics), so that the material is delivered effectively. This research effectively. This research is a literature study Methods of collecting basic reference data and books to study literacy and STEAM in the Independent Learning Curriculum through Bloom Taxonomy.